Formación para la planeación territorial regional de los municipios del CIT (2011)
The land use and planning ae key issues fo the development of municipalities theefoe seeks individuals with the capacity to fom citical of planning, in this pape show the essential themes that must be appopiated by the plannes, in addition to final design a cuiculum fo them.